INDUCED FUCTIONAL MALE OF CORAL TROUT GROUPER (Plectropomus leopardus) USING 17α-METHYLTESTOSTERONE HORMONE - Sar Budi Moria Sembiring; Jhon Harianto Hutapea; Ida Komang Wardana; Ahmad Muzaki; Indah Mastuti (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2013)
The success of grouper seeds production is depends on the availability of qualified broodstock. The nature of grouper is protogynous hermaphrodite, causing difficulties to mantain female and a bit difficult to get male broodstock, one possibility to accelerate sex revers is by hormone manipulation. The aim of this experiment was to find effectiveness of 17α-methyl testosterone hormone to produce coral trout grouper (Plectropomus leopardus) functional male. The experiment was conducted in floating net cage by using 6 net cages with size of 2 m x 2 m x 2 m at density of 25 fish/cage, size of fish were 377.27±21.49 g. The fishes were treated by hormone implantation at concentration of 50 μg/kg body weight and without hormone implantation as a control with 3 replicates. The results showed that the highest concentration of testosteron in fish blood (1.144±0.135 pg/mL) was detected after four months of hormone treatment, but the concentration of testosteron in fish blood declined after 8th months of treatment. The treated fish with hormone grew faster than control. Based on histological analysis of gonad, female gonado somatic index was higher for treated fish compare to control. Its seems that hormone tratment lead to promote development of female maturity and than sex reverse into male become faster.